Factors Related to Safety Riding Behavior Among Students of SMA Negeri 2 Indramayu in 2023 - Linda Iryani; Riyanto; Ade Rahmawati; Tating Nuraeni; Aman Evendi (Penerbit Hellow Pustaka, 2025)
Data from the Central Statistics Agency (BPS) 2023 shows an increase in traffic accidents in Indonesia with 155 thousand cases, and 66 thousand came from students, with motorbikes dominating (74.35%). Data from the Indramayu Police Traffic Unit in 2023 noted that 34 cases of traffic accidents involved high school students. Efforts to reduce traffic accidents include implementing safety riding behavior. SMA Negeri 2 Indramayu still has students who drive at high speed, despite the socialization by the Indramayu police regarding safety riding. This study aims to determine the factors associated with safety riding behavior in high school students of SMA Negeri 2 Indramayu in 2023. The results showed that there was a relationship between knowledge and safety riding behavior with a p-value of 0.021, there was a relationship between attitude and safety riding behavior with a p-value of 0.044, there was no relationship between helmet availability and safety riding behavior with a p-value of 0.130, and there was a relationship between social environmental support and safety riding behavior with a p-value of 0.018. Thus there are factors related to safety riding behavior, namely knowledge, attitudes and social environmental support.